Complement Profiles in Patients with Amyotrophic Lateral Sclerosis: A Prospective Observational Cohort Study - Kjældgaard AL (Dove Medical Press, 2021)
Anne-Lene Kjældgaard,1,2 Katrine Pilely,1 Karsten Skovgaard Olsen,2 Anne Øberg Lauritsen,2 Stephen Wørlich Pedersen,3 Kirsten Svenstrup,3,4 Merete Karlsborg,4 Helle Thagesen,5 Morten Blaabjerg,5 Ásta Theódórsdóttir,6 Elisabeth Gundtoft Elmo,3 Anette Torvin Møller,7 Niels Anker Pedersen,8 Niels Kirkegaard,8 Kirsten Møller,2,9 Peter Garred1,9 1Laboratory of Molecular Medicine, Department of Clinical Immunology, Section 7631, Diagnostic Centre, Rigshospitalet, Copenhagen, Denmark; 2Department of Neuroanaesthesiology Neuroscience Centre, Rigshospitalet, Copenhagen, Denmark; 3Department of Neurology, Neuroscience Centre, Rigshospitalet, Copenhagen, Denmark; 4Department of Neurology, Bispebjerg Hospital, Copenhagen, Denmark; 5Department of Neurology, Roskilde University Hospital, Roskilde, Denmark; 6Department of Neurology, Odense University Hospital, Odense, Denmark; 7Department of Neurology, Aarhus Hospital, Copenhagen, Denmark; 8Department of Anaesthesiology, Private Hospital Gildhøj, Brondby, Denmark; 9Institute of Clinical Medicine, Faculty of Health and Medical Sciences, University of Copenhagen, Copenhagen, DenmarkCorrespondence: Anne-Lene KjældgaardLaboratory of Molecular Medicine, Department of Clinical Immunology, Section 7631, Diagnostic Centre, Rigshospitalet, Ole Maaloesvej 26, Copenhagen, DK-2200, DenmarkTel +45 35457631Fax +45 35398766Email anne-lene.kjaeldgaard@regionh.dkBackground: The complement system has been suggested to be involved in the pathophysiology of amyotrophic lateral sclerosis (ALS), a progressive motor neuron disease. In the present study, we compared levels of selected complement markers to clinical outcome in ALS patients.Methods: This observational, explorative cohort study included 92 ALS patients, 61 neurological controls (NCs) admitted for suspected aneurysmal subarachnoid haemorrhage, and 96 neurologically healthy controls (NHCs). Peripheral blood and cerebrospinal fluid (CSF) were obtained for the measurement of ficolin-1, − 2, and − 3; collectin-11, MBL, MASP-3, MAP-1, C4, C3, PTX-3, and complement activation products C4c, C3bc, and sC5b-9. We recorded clinical outcomes of ALS patients for 24 to 48 months after inclusion in order to analyse the effects of the complement markers on survival time.Results: Compared with both control groups, ALS patients exhibited increased collectin-11, C4 and sC5b-9 in plasma, as well as increased ficolin-3 in CSF. Ficolin-2 was significantly decreased in plasma of the ALS patients compared with NHCs, but not with NCs. The concentration of collectin-11, C3 and C3bc correlated negatively with the revised ALS functional rating scale (ALSFRS-R). No association was found between levels of complement markers and survival as estimated by hazard ratios.Conclusion: ALS patients exhibit aberrant expression of selected mediators of the lectin complement pathway as well as increased activation of the terminal complement pathway, corroborating the notion that the complement system might be involved in the pathophysiology of ALS.Keywords: amyotrophic lateral sclerosis, innate immunity, complement, lectin pathway, cerebrospinal fluid, pathophysiology, observational cohort study